Crowding in School Choice - Phan, William; Tierney, Ryan; Zhou, Yu (American Economic Review, 2024)
We consider the market design problem of matching students to schools in the presence of crowding effects. These effects are salient in parents’ decision-making and the empirical literature; however, they cause difficulties in the design of satisfactory mechanisms and, as such, are not currently considered. We propose a new framework and an equilibrium notion that accommodates crowding, no-envy, and respect for priorities. The equilibrium has a student-optimal element that induces an incentive-compatible mechanism and is implementable via a novel algorithm. Moreover, analogs of fundamental structural results of the matching literature (the rural hospitals theorem, welfare lattice, etc.) survive. (JEL D47, H75, I21, I28)